2019
DOI: 10.1242/bio.041533
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in metabolic rate and its correlation with local environment in the Chinese scorpionMesobuthus martensii

Abstract: Scorpions are well known for their reduced resting metabolic rate (RMR) in comparison to typical arthropods. Since RMR is a key physiological trait linked with evolutionary fitness, it is expected that there may exist intraspecific RMR variation given the ecological and geographical heterogeneities across the distributional range of a species. Nevertheless, it is unclear whether RMR variation exists among scorpion populations. Here, we compared the RMR (VCO 2 ) of 21 populations of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Due to the wide distribution range and complex habitat of this species, a more extensive sampling is clearly needed for rigorously examining intraspecific diversification and evolution in M. martensii [12]. Intraspecific resting metabolic rate, a key physiological trait linked with evolutionary fitness, shows that variation exists in between sexes and among populations of M. martensii that is closely related to the local mean temperature and mean annual days of rainfall [13]. Our findings in the expression differences of toxin gene families between genders and among populations of M. martensii suggest a similar case to the relevance to the environment to resting metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the wide distribution range and complex habitat of this species, a more extensive sampling is clearly needed for rigorously examining intraspecific diversification and evolution in M. martensii [12]. Intraspecific resting metabolic rate, a key physiological trait linked with evolutionary fitness, shows that variation exists in between sexes and among populations of M. martensii that is closely related to the local mean temperature and mean annual days of rainfall [13]. Our findings in the expression differences of toxin gene families between genders and among populations of M. martensii suggest a similar case to the relevance to the environment to resting metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that M. martensii formed four branches in China: east China subclade, central north China subclade, isolated east China subclade, and widespread subclade [12]. In addition, Wang et al (2019) analyzed the relationship between metabolic rate and the environment in 21 localities of M. martensii in China and revealed significant differences in the resting metabolic rate between sexes from the same locality and among different populations [13]. Similarly, reported differences in the expression patterns of toxin genes in different populations from four localities (Hebei, Henan, Shandong, and Shanxi Provinces) and genders (from Gansu Province) of M. martensii [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…Owing to their extraordinary biology and ecology, scorpions become a promising model for biogeographic studies in historical geo-climatic context ( Bryson et al 2013a ; Shi et al 2013 ; Ceccarelli et al 2016 ; Dolby et al 2019 ), especially for various drylands in Central Asia ( Graham et al 2012 , 2019 ), Middle East ( Alqahtani et al 2022 ), North Africa ( Cain et al 2021 ), southwestern North America ( Bryson et al 2013b ; Graham et al 2013a , b ; Miller et al 2014 ), and South American Pacific Coast ( Ceccarelli et al 2017 ). They represent an iconic and charismatic lineage of arthropods ( Sharma et al 2015 ), well known for some of their unique biological characteristics, including morphological conservatism ( Sissom 1990 ), low resting metabolic rate ( McCormick and Polis 1990 ; Wang et al 2019 ), and unusual life history that are more similar to those of long-lived vertebrates ( Gantenbein and Largiadèr 2002 ). These features collectively enable scorpions to survive the drastic environmental changes and mass extinctions over the past 425 million years ( Polis 1990 ).…”
mentioning
confidence: 99%